Development of an AmpliSeqTM Panel for Next-Generation Sequencing of a Set of Genetic Predictors of Persisting Pain - Kringel, Dario; Kaunisto, Mari A.; Lippmann, Catharina; Kalso, Eija; Lötsch, Jörn (Frontiers in Pharmacology, 2018)
Background: Many gene variants modulate the individual perception of pain and possibly also its persistence. The limited selection of single functional variants is increasingly being replaced by anal-yses of the full coding and regulatory sequences of pain-relevant genes accessible by means of next generation sequencing (NGS). Methods: An NGS panel was created for a set of 77 human genes selected following different lines of evidence supporting their role in persisting pain. To address the role of these candidate genes, we established a sequencing assay based a custom AmpliSeq™ panel to assess the exomic sequences in 72 subjects of Caucasian ethnicity. To identify the systems biology of the genes, the biological func-tions associated with the expression of these genes and their respective products were Results: Sequencing generated a median of 2.85 • 106 reads per run with a mean depth close to 200 reads, mean read length of 205 called bases and an average chip loading of 71 %. A total of 3,185 genetic variants were called. A computational functional genomics analysis indicated that the pro-posed NGS gene panel covers biological processes identified previously as characterizing the func-tional genomics of persisting pain. Conclusions: Results of the NGS assay suggested that the produced nucleotide sequences compara-ble to those earned with the classical Sanger sequencing technique. The assay is applicable for small to large-scale experimental setups to target the accessing of information about any nucleotide within the addressed genes in a study cohort.